Worldwide Argus II implantation: recommendations to optimize patient outcomes. Issue 1 (December 2016) - Ghodasra, Devon; Chen, Adrienne; Arevalo, J.; Birch, David; Branham, Kari; Coley, Brian; Dagnelie, Gislin; de Juan, Eugene; Devenyi, Robert; Dorn, Jessy; Fisher, Andy; Geruschat, Duane; et al.
Abstract Background A position paper based on the collective experiences of Argus II Retinal Prosthesis System investigators to review strategies to optimize outcomes in patients with retinitis pigmentosa undergoing retinal prosthesis implantation. Methods Retinal surgeons, device programmers, and rehabilitation specialists from Europe, Canada, Middle East, and the United States were convened to the first international Argus II Investigator Meeting held in Ann Arbor, MI in March 2015. The recommendations from the collective experiences were collected. Factors associated with successful outcomes were determined. Results Factors leading to successful outcomes begin with appropriate patient selection, expectation counseling, and preoperative retinal assessment. Challenges to surgical implantation include presence of staphyloma and inadequate Tenon's capsule or conjunctiva. Modified surgical technique may reduce risks of complications such as hypotony and conjunctival erosion. Rehabilitation efforts and correlation with validated outcome measures following implantation are critical. Conclusions Bringing together Argus II investigators allowed the identification of strategies to optimize patient outcomes. Establishing an on-line collaborative network will foster coordinated research efforts to advance outcome assessment and rehabilitation strategies.